Differentiated Instruction as a Form of Merdeka Belajar in Arabic Language Learning - Rahmawati, Nailur; Al-Muayyad, Mohammad Nasrul Fata; Rohmah, Kholifatur; Fitri, Aisyah Najwa Noor; Damayanti, Annisa (Arabiyatuna: Jurnal Bahasa Arab, 2024)
The purpose of this study is to examine and describe the concepts and principles of differentiated instruction models and examples of their implementation in Arabic language learning. This is an effort to determine practical procedural steps that can be taken and followed by Arabic language teachers to benefit from differentiated instruction. Through differentiated instruction, it is expected that the role of the teacher is not just to exhaust the material, but to optimize the learning process of each student; differentiation becomes a prerequisite for the learning process, not just an additional element that is “nice to have”. To achieve this goal, this research uses a literature study approach with an inductive descriptive method design to present views and theories about differentiated instruction and how it is applied in Arabic language learning. With this approach, this research seeks to explore theories and opinions regarding differentiated instruction models, analyze them, and utilize them to be used as procedural steps in Arabic language learning. The results of this research indicate that the differentiated instruction model can be a learning solution that can be implemented to answer the needs of diverse students. Differentiated instruction is learning that begins with a diagnostic assessment to map the characteristics of students so that teachers are able to design learning well according to students' needs. Differentiated instruction can be applied through content, process and product aspects. It is hoped that the results of this research can provide benefits for teachers and provides insight into the application of differentiated instruction in Arabic language learning.   Keywords: Differentiated learning model, Arabic learning, Merdeka belajar